State Of Research Of Certain Aspects Of Female Criminality In Ukraine - Havlovska, Alina; Dzyurbel, Andriy (Archives of Criminology and Forensic Sciences, 2023)
Research paper is devoted to the analysis of research on certain aspects of female crime in Ukraine. The article focuses on spectrum systematization of theoretical and practical issues in the field of female crime presented by scientists. The results of relevant scientific research were analyzed by examining the texts of dissertation abstracts, monographs, scientific articles, dissertations and other research papers. The main attention is paid to analysis of research papers of Ukrainian scientists in recent years. The article systematizes according to research areas (criminal-legal characteristics of crimes committed by women; criminological characteristics of female criminals and female crime; criminal and executive aspects of serving a criminal sentence by convicted women) and groups of problematic issues in this field (criminal law characteristics of certain types criminal offenses committed by women, criminal and legal correction of convicted women, criminal-legal and criminological characteristics of female crime, prevention and countermeasures against female crime, etc.).